Parental concerns about school reopening during COVID-19 pandemic at Bharatpur, Chitwan - Sigdel, Dipa; Joshi, Alisha; Kumar Mehta, Raj; Sharma, Kalpana (Journal of Chitwan Medical College, 2024)
Background: During the Corona Virus Infection Disease 2019 (COVID-19) pandemic, educational sectors were highly influenced worldwide. Educational authorities decided to close schools and adopt online learning as an alternative option. Parental concern for child safety during school reopening became an essential consideration. Hence, this study aimed to assess the parental concern about school reopening during COVID-19 in Bharatpur, Chitwan.Method: A cross-sectional web-based survey was carried out among parents whose children were studying in three private schools in the Chitwan district, Nepal. The sample was selected using the convenience sampling technique. Ethical approval was obtained. Data were collected using a structured self-administered questionnaire from 28 Jan 2022 to 7 Feb 2022. The questionnaire was made available through Google form in the Nepali version. Data were analyzed using IBM SPSS version 20. A chi-square test was applied to measure the association between parental concern and selected variables. Statistical significance was set at